Serum Osteopontin, KL-6, and Syndecan-4 as Potential Biomarkers in the Diagnosis of Coal Workers’ Pneumoconiosis: A Case–Control Study - Hou Z; Zhang X; Gao Y; Geng J; Jiang Y; Dai H; Wang C (Dove Medical Press, 2023)
Zhifei Hou,1,2 Xinran Zhang,3 Yong Gao,4 Jing Geng,2 Yu Jiang,5 Huaping Dai,1,2 Chen Wang1,2 1Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 2Department of Pulmonary and Critical Care Medicine, Center of Respiratory Medicine, China-Japan Friendship Hospital; National Center for Respiratory Medicine; National Clinical Research Center for Respiratory Diseases; Institute of Respiratory Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 3Department of Clinical Research and Data Management, Center of Respiratory Medicine, China-Japan Friendship Hospital; National Center for Respiratory Medicine; National Clinical Research Center for Respiratory Diseases; Institute of Respiratory Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 4Department of Pulmonary and Critical Care Medicine, Sinopharm Tongmei General Hospital, Datong, Shanxi Province, People's Republic of China; 5Biomedical Innovation Center, Beijing Shijitan Hospital, Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Huaping Dai; Chen Wang, Email daihuaping@ccmu.edu.cn; cyh-birm@263.netBackground: Coal worker's pneumoconiosis (CWP) is a chronic occupational disease mainly caused by coal dust inhalation in miners. This study aimed to investigate the clinical value of Osteopontin (OPN), KL-6, Syndecan-4 and Gremlin-1 as serum biomarkers in CWP.Patients and Methods: We integrated reported lung tissues transcriptome data in pneumoconiosis patients with silica-exposed alveolar macrophage microarray data to identify four CWP-associated serum biomarkers. The serum concentrations of Osteopontin, Krebs von den Lungen-6 (KL-6), Syndecan-4 and Gremlin-1 were measured in 100 healthy controls (HCs), 100 dust-exposed workers (DEWs) and 200 patients of CWP. Receiver operating characteristic (ROC) curve analysis was used to determine the sensitivity, specificity, cut-off value and area under the curve (AUC) value of biomarkers.Results: The pulmonary function parameters decreased sequentially, and the serum OPN, KL-6, Syndecan-4 and Gremlin-1 concentrations were increased sequentially among the HC, DEW and CWP groups. Among all participants, multivariable analysis revealed that these four biomarkers were negatively correlated with the pulmonary function parameters (all p< 0.05). Compared with HCs, patients with higher OPN, KL-6, Syndecan-4 and Gremlin-1 had higher risk for CWP. The combination of OPN, KL-6, and Syndecan-4 can improve the diagnostic sensitivity and specificity of CWP patients differentiated from HCs or DEWs.Conclusion: OPN, KL-6 and Syndecan-4 are novel biomarkers that can be used for CWP auxiliary diagnosis. The combination of three biomarkers can improve the diagnostic values of CWP.Keywords: coal workers' pneumoconiosis, biomarker, osteopontin, Krebs von den Lungen-6, Syndecan-4, Gremlin-1